Measuring De Facto Financial Openness: A New Index - Andreas Christian Steiner; Torsten Saadma (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The sum of foreign assets and liabilities over GDP has been proposed as a measure of de facto financial openness (Lane and Milesi-Ferretti, 2003, 2007). It has been widely used in empirical applications, both as dependent variable and covariate explaining, for instance, economic growth, crisis incidence and economic productivity. This paper proposes an adjusted measure called private financial openness: Large inflows of development aid or central banks' stocks of reserves do not stem from private investors' decisions and are excluded from this measure. In this sense, private financial openness quantifies private agents' willingness and ability to invest abroad and to incur foreign debt. We show statistically that our measure differs significantly from the standard one in developing countries and in emerging markets, in the latter group especially since the 2000s. To highlight the importance of the new index, we use a cross-country panel data set to estimate standard regressions of the relationship between financial openness and economic growth and show the both measures may lead to opposing conclusions.
Keywords: F36; F43; O47; 330